Prevalence of Myocardial Injury and Myocardial Infarction in Patients with a Hypertensive Emergency: A Systematic Review - Mohammed A. Talle; Ellen Ngarande; Anton F. Doubell; Philip G. Herbst (Diagnostics, 2022)
Myocardial injury and myocardial infarction can complicate a hypertensive emergency, and both are associated with poor prognosis. However, little is known about the prevalence of myocardial injury and the different subtypes of myocardial infarction in patients with hypertensive emergencies. This systematic review aims to determine the prevalence of myocardial infarction and its subtypes, and the prevalence of myocardial injury in patients with hypertensive emergencies following the PRISMA guideline. A systematic search of PubMed, Web of Science, and EBSCOHost (MEDLINE) databases was carried out from inception to identify relevant articles. A total of 18 studies involving 7545 patients with a hypertensive emergency were included. Fifteen (83.3%) studies reported on the prevalence of myocardial infarction ranging from 3.6% to 59.6%, but only two studies specifically indicated the prevalence of ST-elevation and non-ST-elevation myocardial infarction. The prevalence of myocardial injury was obtained in three studies (16.7%) and ranged from 15% to 63%. Despite being common, very few studies reported myocardial injury and the subtypes of myocardial infarction among patients presenting with a hypertensive emergency, highlighting the need for more research in this area which will provide pertinent data to guide patient management and identify those at increased risk of major adverse cardiovascular events.